Historical Materialist Approach to Literature and Art - Khatri, Tilak Bahadur (Contemporary Research: An Interdisciplinary Academic Journal, 2024)
This article explores the basic features of the historical materialist approach to literature and art. It aims to highlight the core of this approach to literature and art and make a contrast to other approaches. The article addresses the research problems concerning the view of the historical materialist approach to the primacy of being or consciousness, the relationship of literature and art with the objective world, the free or class partisan literature and art, and the role of literature and art in changing the existing society. The research methodology adopted for this study is the review-based analysis of some of the major critiques of the historical materialist approach to literature and art. The researcher has included the critiques of Karl Marx, Frederick Engels, V.I. Lenin, and Mao Tsetung as they represent the founding figures of the approach and widely named this approach the Marxist approach too. The article reveals that the historical materialist approach views being as primary over consciousness, observes the literature and art as the reflection of the objective world, believes in the class partisan literature and art in a class-based society, and sees the prime utility of literature and art in bringing a radical change in society. The historical materialist approach favors the revolutionary literature and art that takes sides with the majority of working-class people, the revolutionary force of the future capable of establishing the scientific communist society.